Use of nano titanium hydroxide and nano zirconium hydroxide fixed filter paper for rapid detection of Staphylococcus aureus in dairy products by PCR without pre-enrichment. (June 2023) - Wang, Chun; Zhang, Ruohong; Wang, Xiaofang; Xu, Rui; Yan, Hejing; Li, Xiaoran; Liu, Shaojun; Yin, Shuren; Yao, Hong; Yang, Yang; Cui, Shenghui; Guo, Yunchang
Abstract: Staphylococcus aureus ( S. aureus ) is one of the important pathogens, causing foodborne disease and seriously endangering public health. Therefore, a rapid, reliable, and effective method for detecting S. aureus is urgently needed. In this study, a novel sample pre-treatment that uses a filter paper fixed by nano titanium hydroxide and nano zirconium hydroxide to concentrate target pathogen and eliminate PCR inhibitors was developed, which was coupled with PCR subsequently. The primers targeting the nuc gene of S. aureus were utilized for testing the specificity with 180 strains. Artificially contaminated dairy samples from 10° to 10 4  CFU/25g (mL), including whole milk powder, skim milk powder, cheese, and raw milk, were tested to determine the sensitivity of the method. Natural dairy products were tested to evaluate the application of the developed method compared with the conventional culture method. Further, the stability and application of the reagents used in the developed method was determined, using the reagents stored at −20 °C for 3, 6, and 12 months. The results showed that the specificity of the method was 100% and the detection limit of the method was 10 1  CFU/25g (mL). The PCR method took less than 4 h to complete without pre-enrichment. The application of the PCR method was excellent and the reagents could be stably stored at −20 °C for at least 12 months. In conclusion, the developed method was rapid and sensitive, and can be widely used to detect S. aureus in dairy products and is promising as a precise and high throughput test for the food industry. Highlights: Nano titanium hydroxide and nano zirconium hydroxide fixed filter paper can effectively remove PCR inhibitors. The specificity of the developed method was 100%. The detection limit was 10 1  CFU/25g (mL) and the detection time was 4 h without pre-enrichment. The developed method is suitable for the detection of S. aureus in natural dairy products.